2022
DOI: 10.30541/v55i4i-iipp.675-688
|View full text |Cite
|
Sign up to set email alerts
|

Economic Institutions and Growth Nexus: The Role of Governance and Democratic Institutions—Evidence from Time Varying Parameters’ (TVPs) Models

Abstract: The present study has investigated the channels through which the linkage between economic institutions and growth is gauged, by addressing the main hypothesis of the study that whether quality of governance and democratic institutions set a stage for economic institutions to promote the long-term growth process in Pakistan. To test the hypothesis empirically, our study models the dynamic relationship between growth and economic institutions in a time varying framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Syed et al (2014) further reinforce the notion put forth by Acemoglu et al by examining the role of certain important variables pertaining to institutional quality such as the rule of law, control of corruption and voice and accountability in the economic development of Pakistan revealing their substantial influence on growth rate of the economy. Murtaza and Faridi (2016) explored the multifaceted bond between political institutions, economic growth, and governance in Pakistan. The study advocates that political institutions strongly affect the inherent foundation of economic institutions and eventually the magnitude of the economic growth rate.…”
Section: Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Syed et al (2014) further reinforce the notion put forth by Acemoglu et al by examining the role of certain important variables pertaining to institutional quality such as the rule of law, control of corruption and voice and accountability in the economic development of Pakistan revealing their substantial influence on growth rate of the economy. Murtaza and Faridi (2016) explored the multifaceted bond between political institutions, economic growth, and governance in Pakistan. The study advocates that political institutions strongly affect the inherent foundation of economic institutions and eventually the magnitude of the economic growth rate.…”
Section: Empirical Literaturementioning
confidence: 99%
“…The country appears to perform low on fundamental economic indicators, a deficiency that has its origins in low-quality institutions (Madni and Chaudhary, 2017). The low-quality institutions and poor economic growth are perhaps endogenous where both seem to have mutually reinforced each other over time (Murtaza and Faridi, 2016). Whereas the country possesses rich natural resources endowment, a strategic geographical position and diverse human capital, the nation lags behind its many counterparts in economic growth (Sherani, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The research carried out by Nunn and Wantchekon (2011) and Algan and Cahuc (2010) provided valuable insights into the relationship between institutions, cultural factors, and the persistent existence of economic inequalities. Furthermore, the investigations carried out by Hall and Jones (1999) and Glaeser et al (2004) established that institutional quality has a significant influence on both innovation and productivity Murtaza et al (2016) have examined the pathways responsible for the link between economic growth and institutions. Studies have shown that the caliber of democracy and governance has a substantial influence on the quality of institutions, which in turn play a role in the progress of a nation, along with its unique traditions.…”
Section: Literature Reviewmentioning
confidence: 99%